Taxonomy of Epyris Westwood (Hymenoptera: Bethylidae) from Korea, with the descriptions of ten new species - Lim, Jongok; Lee, Jongwook; Koh, Sanghyun; Lee, Bongwoo; Azevedo, Celso O.; Lee, Seunghwan (Zootaxa, 2011)
Nineteen Epyris species are recorded from Korea. Ten new species: E. aequalis Lim et S. Lee, sp. nov., E. breviclypeatus Lim et S. Lee, sp. nov., E. dulicus Lim et S. Lee, sp. nov., E. finitus Lim et S. Lee, sp. nov., E. jeonbukensis Lim et S. Lee, sp. nov., E. limatulus Lim et S. Lee, sp. nov., E. longiantennatus Lim et S. Lee, sp. nov., E. mureungensis Lim et S. Lee, sp. nov., E. yetus Lim et S. Lee, sp. nov., and E. sudosanensis Lim et S. Lee, sp. nov. are described from Korea. Hitherto unknown females are described for E. fuscipes (Kieffer 1906) and E. yamatonis Terayama 1999. New synonymy is proposed for E. sauteri (Enderlein 1920) = E. formosus Terayama 2006, syn. nov. New combination is proposed for E. fuscipes (Kieffer 1906), comb. nov. (from Rhabdepyris). Seven species: E. asura Terayama 2006, E. darani Terayama 2006, E. fuscipes (Kieffer 1906), E. idaten Terayama 2006, E. niwoh Terayama 2006, E. sauteri (Enderlein 1920), and E. yamatonis Terayama 1999 are recorded for the first time from Korea. Descriptions, illustrations of diagnostic characteristics for each species are presented with a key to the Korean Epyris species.